A New Look at the Coefficients of a Reciprocal Generating Function. (28th August 2014) - Ejsmont, Wiktor
Abstract : We study a special property of free cumulants. We prove that coefficients of a reciprocal generating function correspond to "free cumulants with the first two elements in the same block."